Čingis haan dėlhnijn tüühnėė (šildėg ögüüllijn ėmhtgėl) = Činggis qaġan delekei-yin teüken - Cėrėndorž, Cėgmėdijn; Minžin, Cėrėnbaltavyn 1977- ("Bėmbi San" Hėvlėlijn gazar, 2012)
Collection of articles written by Mongolian historians on Genghis Khan